THE TRANSLATION ANALYSIS ON RIDDLES - Anisa, Ike (MAGISTRA, 2013)
Humor is the tendency of particular cognitive experiences to provoke laughter and provide amusement. People of most ages and cultures respond to humor. The majority of people are able to be amused, to laugh or smile at something funny, and thus they are considered to have a âsense of humor.â One of the kind of humor is riddle. Riddle is a kind of humor that children like to play commonly. They hear other kids ask puzzling questions and then give what appear to be very arbitrary answers that are followed by laughter. So they simply imitate what they hear other kids do. In term of language barrier, problem arises when Indonesia people cannot catch the point of the humor within. For Western, English riddle may be a funny thing because they can catch the point. On the contrary, if riddle is translated literarily into Indonesia, it will lose its point of view because the translation is far from the meaning sense. Keyword: Humor, riddle, translation on riddle